Navigation grade frequency-modulated MEMS accelerometer using internal thermal-piezoresistive amplification - Coelho, Cláudia Alexandra Araújo (2021)
Programa doutoral em Engenharia Eletrónica e de Computadores – Instrumentação e Microssistemas Eletrónicos